Dialysis access procedure training for the nephrologist. Issue 2 (3rd January 2018) - Waheed, Sana; Maursetter, Laura; Yevzlin, Alexander
Abstract: Historically, the placement and maintenance of dialysis access has been an integral part of nephrology training. However, in recent years, a big debate has ensued regarding whether this should be limited to trainees' understanding and counseling the patients regarding indications, alternatives, risks and possible complications of these procedures or should it actually involve more of a hands‐on experience for the trainees. Some of the barriers in making these procedures a requirement across the board are the lack of standardization of procedural training across various training programs and the absence of consensus on what achieving competency in these procedures looks like. However, in the era of declining interest in nephrology, giving up "ownership" of nephrology procedures and increasing reliance on other sub specialties might be a deterrent in attracting residents to this field; we have to make a concerted effort to increase the exposure and opportunities for the trainees to perform these procedures. Moreover, we need to emphasize the implementation of a curriculum for nephrology fellows to evaluate access properly in order to decrease the burden of access related complications. Lastly, we need to continue working towards a more structured curriculum for a dedicated interventional nephrology fellowship for trainees who want to focus on procedures for their long‐term career goals.